PENINGKATAN KEMAMPUAN MENGENAL HURUF VOKAL MELALUI MEDIA POHON HURUF PADA ANAK USIA 3-4 TAHUN DI KELOMPOK BERMAIN STROBERI RESTU 1 MALANG - Aluh Rahmia Maulidya; Anwar Sa’dullah; Yorita Febry Lismanda (UNISMA, 2019)
This study aims to determine to know the increase in the ability to recognize vowels after the use of letter tree media in 3-4 year old children in Restu 1 Strawberry Playing Group Malang. This study used a qualitative descriptive approach and quantitative descriptive analysis with the type of Class Action Research (CAR). The study was conducted in 2 cycles. This study was conducted on 15 children playing the Restu 1 Malang strawberry 2018/2019. Data collection is done by observation techniques, and documentation. Data collection instruments are observation sheets, RPPH, and photos of activities. the results of research that showed an increase in cycle I amount to 33.33% of 15 children who experienced an increase. In the second cycle 86.67% of 15 children experienced an increase.